Rebranding Thai festival / Maziana Mohamad - Mohamad, Maziana (Faculty of Art and Design, 2013)
This study is about the Thai festival that has been held in various parts of Malaysia such as Kelantan Kedah and Terengganu. Many people are not aware of this Thai festival because it was only held in only a few states in Malaysia. Thai Festival brought to Malaysia intending to strengthen the relationship between the people of Thailand and Malaysia. In addition, Malaysian people can to experience the culture, food, traditional performances, handicrafts and others from Thailand. Moreover, the people of Thailand can also feel the culture of Malaysia. The approach used to introduce the Thai festival is to make every advertising in the mass media so this festival is known by the people of Malaysia.